(untitled) (Педагогіка вищої та середньої школи, 2022)
The theoretical analysis periodization different authors (S.B. Branu, L.F. Obukhova, E. Ericson is spent, A.O. Malkin-Pih, K.N. Polivanova, V.L. Slobodchikov ... ). In representation about age crises of development partitioning the period of development on separate stages is initial. And the basic problematic is vagueness of the borders , separating has begun also the end of crisis from adjacent age. As a result of it there was a set of various classifications, and uniform classification and has not been created.